2017
DOI: 10.1093/eurpub/ckw225
|View full text |Cite
|
Sign up to set email alerts
|

Depressed during the depression: has the economic crisis affected mental health inequalities in Europe? Findings from the European Social Survey (2014) special module on the determinants of health

Abstract: Negative implications for mental health (in terms of depressive feelings) have been limited to some of the most strongly affected countries, while in the majority of Europe persons have felt less depressed over the course of the recession. Health inequalities have persisted in most countries during this time with little influence of the recession. Particular attention should be paid to the mental health of the inactive and the precariously employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 22 publications
5
60
0
2
Order By: Relevance
“…More recent evidence showed a more marked worsening of mental health for women in 2014 compared with 2007, but did not take into account intervening years 29. A large study of pan-European data including the UK found no systematic influence of the recession on socioeconomic inequalities in depression up to 2014,30 but did not differentiate between the immediate recessionary period and the period following any economic policy response. Work by Barr et al suggested that from 2009 to 2013 there may have been a widening of socioeconomic inequalities in mental health in the UK 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent evidence showed a more marked worsening of mental health for women in 2014 compared with 2007, but did not take into account intervening years 29. A large study of pan-European data including the UK found no systematic influence of the recession on socioeconomic inequalities in depression up to 2014,30 but did not differentiate between the immediate recessionary period and the period following any economic policy response. Work by Barr et al suggested that from 2009 to 2013 there may have been a widening of socioeconomic inequalities in mental health in the UK 31.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological studies using pan-European data suggest that the direct effect of unemployment on suicide rates was greater in countries with lower social spending,35 and conversely, higher government spending on unemployment support may mitigate adverse impacts on self-rated health 36. On a relative scale the widening of socioeconomic inequalities postausterity is small in the context of long-term trends, particularly by highest qualification (figure 4), and the degree and timing of short-term trends around the recession and austerity period also differ between measures of SEP, possibly explaining the current lack of consensus in the literature 30 31…”
Section: Discussionmentioning
confidence: 99%
“…73 Third, the findings for health inequalities according to income/wealth vary somewhat between the included studies: Some indicate increased inequalities, 60,63,69,78,87,91 whereas others show stability. 75,92,95 Two studies even show decreasing health inequalities between income groups during the crisis, although the decrease is of a negative kind. 81,86 This finding is probably explained, at least partly, by health-related social mobility patterns (see the discussion above).…”
Section: Socioeconomic Indicatorsmentioning
confidence: 99%
“…Twenty-three of the included studies investigate mental health. Despite some noticeable exceptions, 88,91,93,95,99 the main bulk of these studies find increasing socioeconomic inequalities during the Great Recession. From a theoretical perspective, it is reasonable to assume that mental health will be affected for people who lose their jobs and/or worry about how to make ends meet during a crisis.…”
Section: Health Outcomesmentioning
confidence: 99%
“…There is also a need for more research which examines risk and resilience factors at the individual level, as well as wider determinants affecting whole communities (Zivin et al, 2011). Research from an international literature review indicated relatively consistent evidence across Europe showing that suicides increased and mental health deteriorated during the 2008 recession (Parmar et al, 2016) -although not in countries with stronger social security systems (Copeland et al, 2015) -and research using data from the European Social Survey 2006-2014 showed that development of depressive feelings was worse among the precariously employed and economically inactive than for those with unlimited work contracts (Reibling et al, 2017). This is in keeping with a larger evidence base of the effects of previous recessions in the 1980s and 1990s.…”
Section: Background To the Researcha Review Of Existing Evidencementioning
confidence: 99%